Pengaruh Kualitas Pelayanan Terhadap Kepuasan Dan Loyalitas Nasabah Pada LPD Desa Adat Kedonganan - Permana, I Made Aditya Jaya; Nurcahya, I Ketut (E-Jurnal Manajemen, 2014)
ABSTRACT Globalization that happened bring emulation consequence which progressively tighten. To a any company of its effort area of the emulation will always force them to always to give service as well as possible to cutomer, or them will be remained by cutomer. To Lembaga Perkreditan Desa (LPD), one of the all important factor to increase satisfaction of cutomer is by giving service which as well as possible to cutomer or client. This research regarding influence of is quality of service to and satisfaction of loyalitas client at LPD Countryside Custom of Kedonganan. Target of research to know influence of is quality of service to satisfaction of client, influence of satisfaction of client to client loyalty, influence of is quality of service to client loyalty. Method data collecting in this research pass observation method, interview, and kuisioner. This research use primary data and of sekunder, by using two analysis that is descriptive statistic and analysis of inferensial. From this research is obtained by result of that quality of service have an effect on positive to satisfaction of client, satisfaction of client have an effect on positive to client loyalitas, quality of service have an effect on positive to client loyalty. Suggestion able to be given by management and employees shall LPD Countryside Custom of Kedonganan pay attention five dimension of is quality of service especially empathy indicator. Normal 0 false false false EN-GB X-NONE X-NONE
Keywords: Keyword:Service Quality, Satisfaction, Loyalty